“A Forestry Program that Cannot be Equalled in Canada”: Kimberly-Clark’s Extraordinary Silvicultural Project in Northern Ontario, 1928-1976 - Kuhlberg, Mark (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
This article presents the story of the extraordinary reforestation program that was carried out in Kapuskasing by Kimberly Clark after the Second World War. Most historians have argued that the forest industry was only interested in profits and paid little attention to forest management. Kimberley Clark, however, carried out this project for a number of reasons, including its enlightened corporate culture and, most importantly, because it had secured tenure to its timber. The article highlights how foreign firms are not necessarily a danger to Ontario’s forests and underscores those factors that could potentially play a crucial role in tackling the environmental issues we face today.